Blast testing of high performance geopolymer composite walls reinforced with steel wire mesh and aluminium foam. (10th February 2019) - Liu, Jian; Wu, Chengqing; Li, Chunguang; Dong, Wenxue; Su, Yu; Li, Jun; Cui, Ning; Zeng, Fan; Dai, Lan; Meng, Qingfei; Pang, Jiabao
Highlights: Blast tests were conducted on high performance geopolymer composite walls reinforced with steel wire mesh and aluminium foam. Blast performance of high performance geopolymer composite walls was analysed and compared. The damage and the failure modes of the composite walls were analysed. Abstract: Two blast tests were conducted to study the blast resistance of high performance geopolymer composite walls reinforced with steel wire mesh (SWM) and aluminium foam (AF). Conventional reinforced concrete (CRC) walls were also tested as control specimens. In total seven walls were tested under different blast loading conditions. The first blast test was conducted on one 2260 mm × 2260 mm × 150 mm SWM reinforced, one 2260 mm × 1000 mm × 150 mm SWM reinforced and one 2260 mm × 1000 mm × 150 mm combined SWM and AF reinforced high performance geopolymer composite walls under 50 kg TNT explosives at a standoff distance of 2.3 m. The second blast test was conducted on one 2260 mm × 2260 mm × 150 mm SWM reinforced and one 2260 mm × 2260 mm × 150 mm combined SWM and AF reinforced high performance geopolymer composite walls under 100 kg TNT explosives on the ground at the same standoff distance. Blast tests were also performed on two 2260 mm × 2260 mm × 150 mm CRC walls under such two designed explosions to compare their behaviours with reinforced high performance geopolymer composite walls. LVDT (linear variable differential transformer) devices were used to record the deflection histories and pressure sensors were used to measure the airblast pressure histories. The testing results indicated that the combined SWM and AF reinforced high performance geopolymer composite walls had a better blast resistance than the CRC walls, and the SWM reinforced high performance geopolymer composite wall was superior to both.